EVALUASI FAKTOR PENYEBAB PENGEMBALIAN KLAIM BPJS PASIEN RAWAT INAP DENGAN OPTIMALISASI PROFITABILITAS RUMAH SAKIT DI RSUD CIKALONG WETAN - Pujilestari, Intan; Fajriani, Gina; Gunawan, Edih (Jurnal TEDC, 2025)
This concerns the return of claim files from the Social Security Administering Body (BPJS) to the hospital. Problems were found in the Participant Eligibility Letter (SEP) for inpatient care, which was not issued by the BPJS. There was a delay in the issuance or claiming of the SEP by the BPJS from January to April 2023. The research method used was a descriptive method with a quantitative approach. The population consisted of all BPJS inpatient claim files from the last three months at Cikalongwetan Regional General Hospital, totaling 251 files. The sampling technique used was total sampling, with 251 samples. Data collection techniques included observation, interviews, and documentation studies. Data processing techniques were editing and tabulation. Research instruments included stationery, a stopwatch, interview guidelines, a calculator, and a checklist sheet. The research results indicate that Cikalongwetan Regional General Hospital does not yet have written Standard Operating Procedures (SOPs) regarding the implementation of BPJS claims. From the sample data of returned inpatient BPJS claims, totaling 251 files from May to July 2024, in May, the criterion for illegible doctor's handwriting was 98 (36.6%). Therefore, the author suggests regular training and education for medical staff and routine supervision to ensure compliance with Standard Operating Procedures (SOPs).